Characterization of Conventional Dendritic Cells and Macrophages in the Spleen Using the CSF1R-Reporter Transgenic Chickens - Sutton, Kate M.; Morris, Katrina M.; Borowska, Dominika; Sang, Helen; Kaiser, Pete; Balic, Adam; Vervelde, Lonneke (Frontiers in Immunology, 2021)
The spleen is a major site for the immunological responses to blood-borne antigens that is coordinated by cells of the mononuclear phagocyte system (MPS). The chicken spleen is populated with a number of different macrophages while the presence of conventional dendritic cells (cDC) has been described. However, a detailed characterization of the phenotype and function of different macrophage subsets and cDC in the chicken spleen is limited. Using the CSF1R-reporter transgenic chickens (CSF1R-tg), in which cells of the MPS express a transgene under the control elements of the chicken CSF1R, we carried out an in-depth characterization of these cells in the spleen. Immunohistological analysis demonstrated differential expression of MRC1L-B by periarteriolar lymphoid sheaths (PALS)-associated CSF1R-tg+ cells. In the chicken’s equivalent of the mammalian marginal zone, the peri-ellipsoid white-pulp (PWP), we identified high expression of putative CD11c by ellipsoid-associated cells compared to ellipsoid-associated macrophages. In addition, we identified a novel ellipsoid macrophage subset that expressed MHCII, CD11c, MRC1L-B and CSF1R but not the CSF1R-tg. In flow cytometric analysis, diverse expression of the CSF1R-tg and MHCII was observed leading to the categorization of CSF1R-tg cells into CSF1R-tgdim MHCIIinter-hi, CSF1R-tghi MHCIIhi and CSF1R-tghi MHCIIinter subpopulations. Low levels of CD80, CD40, MHCI, CD44 and Ch74.2 were expressed by the CSF1R-tghi MHCIIinter cells. Functionally, in vivo fluorescent bead uptake was significantly higher in the CSF1R-tghi MHCIIhi MRC1L-B+ cells compared to the CSF1R-tgdim and CSF1R-tghi MHCIIinter MRC1L-B+ subpopulations while LPS enhanced phagocytosis by the CSF1R-tghi MHCIIinter subpopulation. The analysis of bead localization in the spleen suggests the presence of ellipsoid-associated macrophage subsets. In addition, we demonstrated the functionality of ex vivo derived CSF1R-tg+ MRC1L-Bneg cDC. Finally, RNA-seq analysis of the CSF1R-tg subpopulations demonstrated that separating the CSF1R-tghi subpopulation into CD11chi and CD11cdim cells enriched for cDC and macrophage lineage cells, respectively while the CSF1R-tghi MHCIIinter subpopulation was enriched for red pulp macrophages. However our analysis could not define the cell lineage of the heterogeneous CSF1R-tgdim subpopulation. This detailed overview of the MPS in the chicken spleen will contribute to future research on their role in antigen uptake and presentation.